Harmful Consequences of Proton Pump Inhibitors on Male Fertility: An Evidence from Subchronic Toxicity Study of Esomeprazole and Lansoprazole in Wistar Rats - Namra Mumtaz; Muhammad Furqan Akhtar; Ammara Saleem; Amjad Riaz (International Journal of Endocrinology)
Proton pump inhibitors (PPIs) are frequently prescribed as gastric acid-suppressing agents. Nevertheless, there is limited evidence supporting the risk of detrimental effects of PPIs on male fertility. The purpose of the current study was to evaluate the effect of subchronic use of proton pump inhibitors on male fertility. Seventy adult male Wistar rats were assigned into seven groups. The normal control group orally received solvent only. Groups 2, 3, and 4 were orally given esomeprazole while groups 5, 6, and 7 received lansoprazole at 2.5, 5, and 10 mg/kg/day, respectively. After 45 days of treatment, blood samples, epididymis, and testis were collected. Sperm count, motility, and morphology were determined. The level of hormones such as testosterone, follicle-stimulating hormone (FSH), and luteinizing hormone (LH) and oxidative status of testis tissue, such as superoxide dismutase, catalase, reduced glutathione, malondialdehyde (MDA), and nitric oxide (NO) were estimated. Results demonstrated a significant decline in sperm count, motility, morphology, testosterone, and catalase at 10 mg/kg/day and GSH at 2.5 mg/kg/day. A significant increase in FSH, LH, and MDA at 10 mg/kg/day and NO at 2.5 mg/kg/day was found as compared to the control group. The pathological alterations specifically dilation of Leydig cells, vacuolization, and degeneration of the seminiferous tubules were also evident. It is concluded that PPIs had caused male reproductive toxicity in Wistar rats due to altered levels of hormones such as testosterone, FSH, and LH, elevated levels of NO, and oxidative stress.